Kcnk3 dysfunction exaggerates the development of pulmonary hypertension induced by left ventricular pressure overload. Issue 12 (23rd January 2021) - Lambert, Mélanie; Mendes-Ferreira, Pedro; Ghigna, Maria-Rosa; LeRibeuz, Hélène; Adão, Rui; Boet, Angèle; Capuano, Véronique; Rucker-Martin, Catherine; Brás-Silva, Carmen; Quarck, Rozenn; Domergue, Valérie; Vachiéry, Jean-Luc; et al.
Abstract: Aims: Pulmonary hypertension (PH) is a common complication of left heart disease (LHD, Group 2 PH) leading to right ventricular (RV) failure and death. Several loss-of-function (LOF) mutations in KCNK3 were identified in pulmonary arterial hypertension (PAH, Group 1 PH). Additionally, we found that KCNK3 dysfunction is a hallmark of PAH at pulmonary vascular and RV levels. However, the role of KCNK3 in the pathobiology of PH due to LHD is unknown. Methods and results: We evaluated the role of KCNK3 on PH induced by ascending aortic constriction (AAC), in WT and Kcnk3 -LOF-mutated rats, by echocardiography, RV catheterization, histology analyses, and molecular biology experiments. We found that Kcnk3 -LOF-mutation had no consequence on the development of left ventricular (LV) compensated concentric hypertrophy in AAC, while left atrial emptying fraction was impaired in AAC- Kcnk3 -mutated rats. AAC-animals (WT and Kcnk3 -mutated rats) developed PH secondary to AAC and Kcnk3 -mutated rats developed more severe PH than WT. AAC- Kcnk3 -mutated rats developed RV and LV fibrosis in association with an increase of Col1a1 mRNA in right ventricle and left ventricle. AAC- Kcnk3 -mutated rats developed severe pulmonary vascular (pulmonary artery as well as pulmonary veins) remodelling with intense peri-vascular and peri-bronchial inflammation, perivascular oedema, alveolar wall thickening, and exaggerated lung vascular cell proliferation compared to AAC-WT-rats. Finally, in lung, right ventricle, left ventricle, and left atrium of AAC- Kcnk3 -mutated rats, we found a strong increased expression of Il-6 and periostin expression and a reduction of lung Ctnnd1 mRNA (coding for p120 catenin), contributing to the exaggerated pulmonary and heart remodelling and pulmonary vascular oedema in AAC- Kcnk3 -mutated rats. Conclusions: Our results indicate that Kcnk3 -LOF is a key event in the pathobiology of PH due to AAC, suggesting that Kcnk3 channel dysfunction could play a potential key role in the development of PH due to LHD. Graphical Abstract: